Event-Related Potentials in ADHD Associated With Tuberous Sclerosis Complex: A Possible Biomarker of Symptoms Severity? - Moavero, Romina; Marciano, Sara; Pro, Stefano; De Stefano, Donata; Vigevano, Federico; Curatolo, Paolo; Valeriani, Massimiliano (Frontiers in Neurology, 2020)
Background and aim. Tuberous Sclerosis Complex (TSC) is associated with a high rate of attention deficit - hyperactivity disorder (ADHD), usually with more severe symptoms than in idiopathic cases. Event related potentials have been used in idiopathic ADHD, and they have been proposed as a possible biomarker of symptoms severity. Aim of this study was to investigate ERP characteristics in patients with ADHD secondary to TSC, compared to patients with drug naïve idiopathic ADHD and healthy controls (HC), to investigate whether: 1) distinct clinical features can be due to different pathophysiological mechanisms, and 2) ERPs may reliably predict ADHD symptoms severity in TSC. Materials and methods. We enrolled 6 patients with idiopathic ADHD (iADHD), 13 patients with ADHD associated with TSC (tscADHD), and 14 age-matched HC (7-17 years). All of them underwent ERP recording, with mismatch negativity (MMN) preceding the P300 recording. All patients underwent neurocognitive evaluations. Results. MMN latency was shorter in iADHD (p=0.04) and tscADHD (p=0.06) than in HC, with no difference between patients’ groups. MMN amplitude was significantly higher in patients (both iADHD and tscADHD) than in HC. The P300 amplitude was significantly lower in iADHD patients than in both tscADHD patients (p=0.03) and HC (p<0.001). No difference was found between tscADHD patients and HC (p=0.2). Conclusion. While patients with iADHD present lower P300 amplitude than HC, in tscADHD patients P300 amplitude was not different from that in HC, suggesting that in TSC P300 amplitude does not really reflect symptom severity.